Do not believe the hype: Using case studies and experimental evidence to show why the HSE is wrong about excluding deflagration‐to‐detonation transitions. Issue 2 (22nd October 2018) - Davis, Scott; Pagliaro, John; Botwinick, Drew; DeBold, Thomas; van Wingerden, Kees; Allason, Dan; Johnson, D. Michael
Abstract : A recent report by the UK's Health and Safety Executive postulated that severe explosions can propagate at subsonic speeds but generate overpressures of several bar in open areas and this "new" type of explosion is episodic in nature. The UK Health and Safety Executive (HSE) paper based their findings on a specific interpretation of historical data and "empirical evidence" from previous incidents and selected experimental data. They indicate that their results should guide plant design and risk assessment. The report fails to take account of key evidence from recent large‐scale experimental studies and incident investigations in proposing a hypothetical explosion mechanism over those that are known to occur and are well understood. This has the potential to misdirect efforts to manage such events. The first part of the article will review a number of incidents and demonstrate that each of these incidents can indeed be explained by fast deflagrations or transition to detonations, in complete contradiction to the HSE findings. The results found at the incident sites will be directly compared against results from recent DDT work and damage. The second part of the paper will present a novel technique for determining the DDT transition velocity from high‐speed video footage of experiments performed at large scales. © 2018 American Institute of Chemical Engineers Process Saf Prog 38: e11998, 2019